Early Childhood Education and Care : A Focused Review of Preschool Education in Tajikistan - World Bank (World Bank, Washington, DC, 2019)
Tajikistan’s human capital, eroded by the country’s civil war (1992–97), remains low today. According to analyses by the World Bank’s Human Capital Project, a child born in Tajikistan today is expected to be 53 percent as productive as he or she could be with full health and complete education. High rates of childhood stunting, low preschool coverage and low learning outcomes are the major reasons for underperformance. Accordingly, Tajikistan has made it a development priority to invest in high quality early childhood development (ECD) and early childhood education and care (ECEC). Given Tajikistan’s overwhelmingly young population and high birth rates (box W1), the government is right to address its human capital shortcoming by investing in its youth. High quality ECD and ECEC investments are vital: they yield high economic and social returns by improving child health, education access and quality, and cognitive and psychosocial development.